Usefulness of Combining NT-proBNP Level and Right Atrial Diameter for Simple and Early Noninvasive Detection of Pulmonary Hypertension Among Adult Patients with Atrial Septal Defect - Hartopo, Anggoro Budi (Indonesian Society of Internal Medicine, 2022)
Background: Atrial septal defect developed pulmonary hypertension (ASD-PH) at first diagnosis due to late presentation are common in Indonesia. Transthoracic echocardiogram (TTE) is a common tool to detect ASD-PH, before proceeding to invasive procedure. The NT-proBNP measurement to screen ASD-PH is not yet considered the standard approach, especially in limited resource conditions. The objective of this study is to assess the value of NT-proBNP, along with simple TTE parameter, to screen PH among adults with ASD. Methods: This was a cross-sectional study. The subjects were adult ASD-PH patients from the COHARD-PH registry (n=357). Right heart catheterization (RHC) was performed to diagnose PH. Blood sample was withdrawn during RHC for NT-proBNP measurement. The TTE was performed as standard procedure and its regular parameters were assessed, along with NT-proBNP, to detect PH. Results: Two parameters significantly predicted PH, namely NT-proBNP and right atrial (RA) diameter. The cut-off of NT-proBNP to detect PH was ≥140 pg/mL. The cut-off of RA diameter to detect PH was ≥46.0 mm. The combined values of NT-proBNP level ≥140 pg/mL and RA diameter ≥46.0 mm yielded 46.6 sensitivity, 91.8 specificity, 54.3 accuracy, 96.5 positive predictive value and 26.2 negative predictive value to detect PH, which were better than single value. Conclusion: NT-proBNP level ≥140 pg/mL represented PH in adult ASD patients. The NT-proBNP level ≥140 pg/mL and RA diameter ≥46.0 mm had a pre-test probability measures to triage patients needing more invasive procedure and also to determine when and if to start the PH-specific treatment. © 2022, Indonesian Society of Internal Medicine. All rights reserved.